2022
DOI: 10.1186/s12960-022-00787-0
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization, death, and probable reinfection in Peruvian healthcare workers infected with SARS-CoV-2: a national retrospective cohort study

Abstract: Background Peru has some of the worst outcomes worldwide as a result of the SARS-CoV-2 pandemic; it is presumed that this has also affected healthcare workers. This study aimed to establish whether occupation and other non-occupational variables were risk factors for possible reinfection, hospitalization, and mortality from COVID-19 in cohorts of Peruvian healthcare workers infected with SARS-CoV-2. Methods Retrospective cohort study. Healthcare w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our investigation revealed a COVID-19 recurrence rate of 15%, signifying a substantial rate of recurrence in Iran. In comparison, prior studies have reported varying reinfection rates among HCWs, ranging from 5.94-20.57%, with notable differences potentially arising from variations in diagnostic certainty and the inclusion of probable cases (11)(12)(13)(14)(15). The criteria used to de ne recurrence or reinfection based on the time interval between positive SARS-CoV-2 tests may also contribute to these disparities.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our investigation revealed a COVID-19 recurrence rate of 15%, signifying a substantial rate of recurrence in Iran. In comparison, prior studies have reported varying reinfection rates among HCWs, ranging from 5.94-20.57%, with notable differences potentially arising from variations in diagnostic certainty and the inclusion of probable cases (11)(12)(13)(14)(15). The criteria used to de ne recurrence or reinfection based on the time interval between positive SARS-CoV-2 tests may also contribute to these disparities.…”
Section: Discussionmentioning
confidence: 94%
“…However, Ramos W. et al reported a higher risk of reinfection among those with direct contact with COVID-19 cases in their work environment. They also found that physicians and nurses had a higher risk of hospitalization compared to other HCWs(15). In addition, physicians and nurses, in the second degree, were at higher risk of hospitalization than other HCWs(15).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…For example, France conducted three reinfection surveys at different periods, with reinfection incidences of 0.08% (June 2020 to February 2021), 0.4% (March 2020 to August 2021), and 3.1% (March 2021 to February 2022), respectively ( 17 19 ). 1.8% of Peruvian healthcare workers might have been reinfected with SARS-CoV-2 between March 2020 and August 2021 ( 20 ). The overall SARS-CoV-2 reinfection incidence was found to be 28.3% (95% CI: 23.7%–33.2%) in Guangdong Province between December 2022 and January 2023 ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence derived from observational studies shows that patients who have recovered from coronavirus disease 2019 (COVID-19) by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can develop natural immunity [ 3 , 4 ]. However, high variability in antibody titers has been documented and healthcare workers seem to be at a high reinfection risk [ 5 , 6 ]. The reinfection risk in these specific population segments seemed to be higher during the dominance of the Omicron variant [ 7 ].…”
Section: Introductionmentioning
confidence: 99%